The regional component of the jargon of street groups of the 1980s and 1990s (based on the speech material of Yoshkar-Ola) - Elena G. Tonkova; Elena S. Yarygina (Publishing house "Sreda", 2023)
The work is devoted to the study of the vocabulary of youth groups in Yoshkar-Ola in 1980-1990. The purpose of this article is to characterize the local features of the language of Yoshkar-Ola youth unofficial groups. The research material was the jargon of participants in street gangs in the capital of the Republic of Mari El at the end of the twentieth century. The sources of language material were documentary literature, journalistic articles, dictionaries of substandard vocabulary and recordings of live speech of former group members. During the research, methods of linguistic observation and description, dictionary interpretation, and contextual analysis of lexical units were used. As a result of the study, the authors come to the conclusion that a number of jargons discussed in the article have become part of the unofficial microtoponymy of the city of Yoshkar-Ola. The likelihood of such lexical units appearing in dictionaries of non-literary vocabulary published by leading publishers is extremely low. The collected material contains information about the etymology of the unofficial toponymy of the city of Yoshkar-Ola, the communicative preferences of local youth and the linguistic realities of 1980-1990. The sublanguage of hooligan youth is very close in nature to Russian argot. A more detailed study of the jargon of street gang members may help change the uncritical attitude of Russian speakers towards the language of the criminal world.